ANALISIS KONDISIFISIK DAN KEMAMPUAN TEKNIK DASAR ATLET FUTSAL JORDUS FUTSAL ACADEMY - Dheo Okto Vernando; Andri Gemaini; Ridho Bahtra; Anggun Permatasari (Jurnal IKEOR, 2025)
The problems encountered in this study include the low physical condition (endurance, speed, and agility) and basic techniques (passing, shooting, dribbling, and controlling) of Jordus Academy futsal athletes. The purpose of this study is to analyze the physical condition and basic techniques of Jordus Academy futsal athletes.. The type of research conducted is quantitative descriptive research. This technique uses survey and test methods. The research location is Rafhely field, Sungayang in July 2025. The population in this study were all Jordus Academy futsal athletes aged 17 with a total of 16 people and sampling by total sampling of 16 people. The research instruments include speed tests (30 meter sprint), agility tests (zigzag run) and endurance tests (interval training) and basic technique measurement tests including passing, dribbling, control and shooting tests. Data analysis techniques use descriptive statistics and t-scores with the help of Ms. Office Excel 2010. The results of the study show that the physical condition of Jordus Academy futsal athletes is in the fairly good category with an average value of 150 and basic techniques are in the category with an average value of 200. So it can be concluded that the basic techniques of Jordus Academy futsal athletes need to be improved to be good. Keywords: Variation, Conventional, Passing, Football Training Methods.Permasalahan yang terdapat pada penelitian ini diantaranya rendahnya kondisi fisik (daya tahan, kecepatan dan kelincahan) dan teknik dasar (passing, shooting, dribbling dan controlling) atlet futsal Jordus Academy. Tujuan penelitian ini yaitu untuk menganalisis kondisi fisik dan teknik dasar atlet futsal Jordus Academy. Jenis penelitian yang dilakukan yaitu penelitian deskriptif kuantitatif. Teknik ini menggunakan metode survey dan test. Tempat penelitian dilapangan Rafhely, Sungayang pada bulan Juli 2025. Populasi dalam penelitian ini adalah seluruh atlet futsal Jordus Academy kelompok pemain umur 17 dengan jumlah 16 orang dan pengambilan sampel dengan cara total sampling sebanyak 16 orang.